Retention Force Comparison Between Hawley and Vacuum-Formed Retainers in Orthodontic Treatment of Maxillary Arch: A Prospective, Non-randomized, Cohort Study over 6 Months - Asadolahi , Erfan; Saleh , Shabnam; Rezaei , Yashar; Hosenzadegan , Mortaza; Behroozian , Ahmad; Sharifi, Reza (Galen Medical Journal, 2024)
Background: This study aimed to investigate the change in the retention force of Hawley and vacuum-formed retainers for the maxillary arch over a 6-month period. Materials and Methods: In this prospective, non-randomized cohort study, 50 patients who were prescribed Hawley or Vacuum-formed retainers for their maxillary arch were consecutively enrolled. Retainers were fabricated to the standardized design on casts and were exclusively checked for every patient. The retention force of retainers was evaluated based on the force (in Grams) required to remove them from the mouth. Retention force was assessed on delivery day, 3 and 6 months after treatment via force gauge. The changes in retention force from one timepoint to another were calculated as a ratio (retention change index) and were then compared between two retainers. Results: forty-five patients (23 Hawley and 22 vacuum-formed) completed the study. The retention force of Hawley retainers throughout three-time points was 453-249-189 (g), while that of vacuum-formed retainers was 857-621-513 (g). The decrease in retention force was statistically significant for both retainers (P value < 0.001). The retention force decrease in Hawley retainers was significantly more than Vacuum-formed retainers throughout 6 months (P value <0.05). Conclusion: Both retainers experienced a loss in retention force over the 6-month period. However, vacuum-formed retainers maintained a higher retention force compared to Hawley retainers, making them more effective in retaining the teeth in their corrected positions.